(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a systematic and detailed examination of the morphemic structure of the English language.It explores the morpheme as the minimal meaningful unit of language, analyzing its core types—free versus bound and lexical versus grammatical—and their distinct functions. The paper delves into the concepts of roots and affixes (prefixes, suffixes, inflections), explicates the phenomenon of allomorphy with phonological conditioning, and illustrates central word-formation processes like derivation and compounding. Furthermore, it discusses the practical implications of morphemic analysis for vocabulary acquisition, spelling, and language teaching. The analysis is supported by concrete linguistic examples, factual data, and established theoretical frameworks.